Analyzing Temperature Distribution in Multiple Fin Geometries to Optimize Heat Transfer Efficiency - Devia Gahana Cindi Alfian; Dicky Januarizky Silitonga (Universitas Sultan Ageng Tirtayasa, 2025)
This study is quantitative research using Computational Fluid Dynamics (CFD) simulations to optimize pin fin design. Samples include aluminum pin fins with three different geometries: circular, square, and cone, and side lengths of 5 mm, 10 mm, and 15 mm. CFD simulations are conducted to quantitatively analyze temperature distribution across the surface and height of the fins. Results show that the highest temperature is localized at the base plate and decreases along the fin height. Circular and square fins demonstrate more uniform temperature distributions, while cone fins show significant gradients between base and tip. Smaller fin side lengths result in greater temperature differences. This research provides a detailed understanding of how fin geometry impacts heat transfer efficiency and temperature distribution, offering valuable insights for the development of more efficient fin designs in thermal management applications.